2020
DOI: 10.1177/0886109920906784
|View full text |Cite
|
Sign up to set email alerts
|

Social Support in Perinatal Grief and Mothers’ Continuing Bonds: A Qualitative Study With Italian Mourners

Abstract: The grieving process after perinatal loss has unique properties. This qualitative study examines one aspect of the grieving process: continuing bonds experienced by the mothers. We offer an interpretative phenomenological analysis of interviews with 15 Italian mothers. Three main relevant themes emerged: “continuing bonds between externalized and internalized presence,” “a difficult guilt to manage,” and “relationships are crucial support systems.” The first one illustrates the ongoing connections to the decea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
2
15
0
4
Order By: Relevance
“…The findings of this study confirm earlier studies that have reported that bereavement leads to relationship changes [7,8,10]. The factors that influenced relationship changes in this study: shame [5,13], the unmet expectation of support [2] and mistrust [2,10] have been confirmed separately by other studies. Of the three factors that influenced the participants' social networks, shame/stigma has received the most attention in stillbirth research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study confirm earlier studies that have reported that bereavement leads to relationship changes [7,8,10]. The factors that influenced relationship changes in this study: shame [5,13], the unmet expectation of support [2] and mistrust [2,10] have been confirmed separately by other studies. Of the three factors that influenced the participants' social networks, shame/stigma has received the most attention in stillbirth research.…”
Section: Discussionsupporting
confidence: 91%
“…As a result of social withdrawal due to stigma, women's social networks may become smaller, disconnected, or underresourced [10][11][12] and their family may emerge as the primary source of support [1,2]. However, the social ramifications of stillbirths extend beyond the family [1,13]. Even if the family was supportive, the bereaved mother would need others outside the family to successfully reintegrate back into society [4].…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature on potential grief following an elective abortion is scarce, and most studies indicate that the majority of women who have elective abortions do not experience significant emotional or mental health problems (28,29). However, some scholars have identified a subgroup of women who are negatively affected by this experience (1,24,(30)(31)(32), particularly young women (33). Scholars explored the possibility that an elective abortion has the potential to elicit a short-term grief response (34).…”
Section: Psychological Problems Related To the Representation Of The Foetus As A Personmentioning
confidence: 99%
“…On the other hand, individuals respond to loss at symbolic as well as biological levels, ascribing significance to the symptoms of separation experienced and to the changes in social relationships caused by the death of a beloved person [ 1 , 2 ]. A major loss, such as the disappearance or death of a loved one, can cause severe grief and carries important consequences for daily life [ 3 , 4 , 5 ]. Mourners experience and express grief uniquely and differently from each other, based on their cultural and family background, life experiences, personal values, and deepest beliefs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%